2021
DOI: 10.1002/bab.2106
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of inhibition effect of butanol and water extracts of Matricaria chamomilla L. on angiotensin‐converting enzyme purified from human plasma

Abstract: Angiotensin-converting enzyme (ACE) liable for the regulation of blood pressure was purified from human plasma by affinity chromatography. Impact of water and butanol extracts of Matricaria chamomilla L. on purity ACE was examined. ACE was purified using the affinity chromatography method. The enzyme activity was evaluated at 345 nm by a spectrophotometer. Extracts of M. chamomilla plant with butanol and water were prepared. Lisinopril was utilized as a specific inhibitor. ACE was purified 3,659-fold from huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…I another study the same group described sheddases able to liberate 65 and 90 kDa ACE isoforms in mesangial cells [52]. Also, in our previous studies, the molecular weight of the ACE enzyme purified from human plasma was found to be 60 and 70 kDa [53,54]. In our work, purity and molecular weight of the ACE enzyme purified from sheep lungs were designated by SDS-PAGE, and two bands, 60 kDa and 70 kDa, were observed on the gel (Figs.…”
Section: Resultsmentioning
confidence: 71%
“…I another study the same group described sheddases able to liberate 65 and 90 kDa ACE isoforms in mesangial cells [52]. Also, in our previous studies, the molecular weight of the ACE enzyme purified from human plasma was found to be 60 and 70 kDa [53,54]. In our work, purity and molecular weight of the ACE enzyme purified from sheep lungs were designated by SDS-PAGE, and two bands, 60 kDa and 70 kDa, were observed on the gel (Figs.…”
Section: Resultsmentioning
confidence: 71%
“…In our previous study, the water and butanol phases of the Juniperus excelsa Bieb. and Matricaria chamomilla L. plants indicated an inhibition effect on ACE purified from human plasma, and IC 50 constants were 5.790, 2.858, 1.292, and 0.353 mg/mL, respectively [42,43]. In another study, the IC 50 values of two synthetic peptides TTP (Thea-Thea-Pro) and gAgAP (GABA-GABA-Pro) showing an inhibitory effect on ACE was determined as 0.92 and 3.4 μmol/L, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Chamomile or Matricaria chamomilla L. is a medicinal plant used worldwide for various ailments (Bas et al, 2021).…”
Section: Matricaria Chamomilla Lmentioning
confidence: 99%
“…The plant has several beneficial constituents for human health, such as flavones, flavanones, and lipophilic actives. These confer numerous biological activities to the plant, such as antioxidant, anti-inflammatory, antiulcerogenic, antimicrobial, anxiolytic and sedative, immunomodulatory, and antihypertensive (Bas et al, 2021;Chauhan et al, 2021).…”
Section: Matricaria Chamomilla Lmentioning
confidence: 99%